(untitled) (MATEMATIKA, 2015)
In this article, a fourth order quartic spline method has been developed to obtain the numerical solution of second order boundary value problem with Dirichlet boundary conditions. The development of the quartic spline method and convergence analysis have been presented. Three test problems have been used for numerical experimentations purposes. Numerical experimentations showed that the quartic spline method generates more accurate numerical results compared with an existing cubic spline method in solving second order boundary value problems.